COVID-19 and social wellbeing in Malaysia: A case study - Yong, Siew Siew; Sia, Joseph (SPRINGER, 2023)
The world has witnessed the largest single disruption to social wellbeing since the first known case of coronavirus disease 2019 (COVID-19) was reported in China in December 2019. In Malaysia, the government implemented the Movement Control Order (MCO) on 18 March 2020 in response to the COVID-19 pandemic. Thus, this paper highlights how the Malaysian government responded to COVID-19 in comparison with some Asian countries; and what has and has not worked for the MCO imposed by the government. The paper adopts a review approach that is supported by findings from both grey and academic literature. The findings reveal that the COVID-19 pandemic has significant impacts on the society’s wellbeing in Malaysia, the most severe of which are negative mental health and job unemployment. On the other hand, COVID-19 has sparked a surge of volunteering in society. This paper presumably and hopefully represents a frontier review with more empirical research to be conducted to investigate the extent of the social impact of COVID-19, the outcomes of which are a call for re-envisioning of social policies in Malaysia. To the best knowledge of the authors, little empirical research has been conducted to explore the social-wellbeing implications of COVID-19 in Malaysia. By reflecting on the various scenarios—both detrimental and beneficial in the context of the COVID-19 pandemic, the paper identifies potential avenues for relevant research in the social wellbeing realm.